CORPORATE SUSTAINABILITY PRACTICES AND FIRMS’ FINANCIAL PERFORMANCE: THE DRIVING FORCE OF INTEGRATED STRATEGIES - MUHAMMAD, ZAHID (2017)
Corporate Sustainability (CS) practices are comparatively mature in developed countries. However, these are yet the matter of concern in developing countries like Malaysia. Accordingly, this study empirically examined integrated strategies and CS practices on firms’ financial performance in Malaysian public listed companies (PLCs). The study employed Two-stage Least Squares (2SLS) and Ordinary Least Square (OLS) to a sample composed of 878 firm-year observations from 2011 to 2013. The findings indicated that there is a significant increase in the level of CS practices and integrated strategies. This increase has been augmented by the government initiatives such as global reporting initiative (GRI), CS awards, and Malaysian Code on Corporate Governance (MCCG) 2012 among others. By further investigating the causal relationship, it is found that CS practices, social and workplace sustainability, as well as integrated strategies, have a significant positive impact on financial performance of the sample firms. Similarly, integrated strategies have an important role in improving CS practices and its various dimensions like social, environmental, workplace and economic sustainability). However, the results could not reveal any relationship between environmental and economic sustainability with firms’ financial performance. Based on the descriptive, normative and instrumental approaches to stakeholder theory, the findings further unveiled that CS practices fully while social and workplace sustainability partially mediate the relationship between integrated strategies and firms' financial performance (ROA). Moreover, social and environmental sustainability partially mediates the association of integrated strategies with firms' financial performance (ROE). Based on findings, the study strongly recommends integrated strategies for addressing the infancy stage of CS practices in Malaysian PLCs. The findings provide important comprehensions for CS practices in emerging economies like Malaysia. Also, the findings provide important insights for all the stakeholders like government practitioners, academia, researchers, banks, Bursa Malaysia, security commission and PLCs.